2023
DOI: 10.1007/s11033-023-08684-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of the gene candidate SecARS encoding alkylresorcinol synthase in Secale

Małgorzata Targońska-Karasek,
Michał Kwiatek,
Jolanta Groszyk
et al.

Abstract: Background Alkylresorcinols (ARs) are compounds belonging to the class of phenolic lipids. A rich source of ARs are cereal grains such as rye, wheat, triticale or barley. ARs found in plants are characterized by a variety of biological properties such as antimicrobial, antifungal and cytotoxic activity. Moreover, they are proven to have a positive influence on human health. Here, we aimed to find and characterize the gene with ARs synthase activity in the species Secale cereale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Jaśkiewicz and Szczepanek [38] showed that, for both winter and spring triticale, there are varietal differences in the content of alkylresorcinols in grain. Similar relationships were found for winter wheat [57,[59][60][61].…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Jaśkiewicz and Szczepanek [38] showed that, for both winter and spring triticale, there are varietal differences in the content of alkylresorcinols in grain. Similar relationships were found for winter wheat [57,[59][60][61].…”
Section: Resultssupporting
confidence: 79%
“…and the lowest in the grain of the population cultivar Amilo (1058 mg•kg −1 d.m.). Studies by Targo ńska-Karasek et al [59] also showed the influence of the genetic factor on the synthesis of alkylresorcinols, while the lowest potential for alkylresorcinol synthesis was demonstrated by the population cultivar Da ńkowskie Złote in comparison to the hybrid cultivar Daniello and the population cultivar L 318. Jaśkiewicz and Szczepanek [38] showed that, for both winter and spring triticale, there are varietal differences in the content of alkylresorcinols in grain.…”
Section: Resultsmentioning
confidence: 91%